Absence of methamphetamine‐induced conditioned place preference in weaver mutant mice - Yuiko Ikekubo; Soichiro Ide; Yoko Hagino; Kazutaka Ikeda (Wiley, 2020)
Abstract Aims G protein‐activated inwardly rectifying potassium (GIRK) channels are related to rewarding effects of addictive drugs. The GIRK2 subunit is thought to play key roles in the reward system. Weaver mutant mice exhibit abnormal GIRK2 function and different behaviors that are caused by several addictive substances compared with wild‐type mice. However, mechanisms of reward‐related alterations in weaver mutant mice remain unclear. The present study investigated changes in the rewarding effects of methamphetamine (METH) in weaver mutant mice. Methods The rewarding effects of METH (4.0 mg/kg) were investigated using the conditioned place preference (CPP) paradigm. Extracellular dopamine level in the nucleus accumbens (NAc) was measured by in vivo microdialysis. To identify brain regions that were associated with these changes in rewarding effects, METH‐induced alterations of Fos expression were investigated by immunohistochemical analysis. Results Weaver mutant mice exhibited a significant decrease in METH‐induced CPP and dopamine release in the NAc. Methamphetamine significantly increased Fos expression in the posterior NAc (pNAc) shell in wild‐type but not in weaver mutant mice. Conclusions Methamphetamine did not induce rewarding effects in weaver mutant mice. The pNAc shell exhibited a significant difference in neuronal activity between wild‐type and weaver mutant mice. The present results suggest that the absence of METH‐induced CPP in weaver mutant mice is probably related to an innate reduction of dopamine and decreased neural activity in the pNAc shell that is partially attributable to the change of GIRK channel function. GIRK channels, especially those containing the GIRK2 subunit, appear to be involved in METH dependence.